Cost-efficient light-weighting within the aviation sector - Carlsson, Mattias (2009)
Rising fuel prices and growing concerns over the impacts of aviation on the greenhouse effect have increased the pressure on the commercial aviation sector to develop measures that improve fuel efficiency. Since commercial aircraft normally remain in service for more than 20 years, it is of interest for aircraft operators to consider fuel efficiency improvements that can be made on existing aircraft. This study develops a method to measure cost efficiency ofreplacing components with light-weight versions of the same component type, in order toreduce aircraft empty weight. Fuel cost reductions arising from weight reductions arediscounted and aggregated over the light-weight components lifetime to produce a net present value (NPV) of the intervention. In addition break-even values (NPV=0) of unit fuel costs,weight reductions, and net investment costs are also derived. Calculations for economy classpassenger seats and catering service trolleys, along with a range of generic intervention scenarios, are conducted. Results show that replacing catering service trolleys is beneficial even at relatively low unit fuel costs -break-even occurs at unit fuel costs between 2 and 24 US$/barrel - while the break-even unit fuel costs for economy class passenger seats ranges from 38 to 359 US$/barrel, depending on the circumstances. Results from generic scenario calculations reveals that - at unit fuel costs of 100 US$/barrel and a component lifetime of 10 years - any intervention with a net investment cost below 1,094 US$ per kg of weight reduction will be profitable.